2015
DOI: 10.1139/cjfr-2014-0344
|View full text |Cite
|
Sign up to set email alerts
|

Estimating forest vulnerability to the next spruce budworm outbreak: will past silvicultural efforts pay dividends?

Abstract: Silvicultural treatments recommended to reduce damage by spruce budworm (SBW; Choristoneura fumiferana Clemens) include reducing balsam fir (Abies balsamea (L.) Mill.) abundance and age and increasing spruce (Picea spp.) and hardwood content. To evaluate the effect of these measures on forest timber supply, we assessed stand characteristics, disturbance history, and timber supply for an intensively managed eastern Quebec forest from 1985 to 2004, encompassing a major SBW outbreak. During this time, mean stand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Currently, sylvicultural practices aim to imitate fire disturbances promoting large clearcuts (Hunter, 1993; National Forest Database [N.F.D], 2016. In order to reduce boreal forest vulnerability to SBW outbreaks, some authors proposed to adapt sylvicultural treatments and forest management promoting the harvesting of the most susceptible stands such as mature fir stands (MacLean, 1980, 1996; Sainte-Marie et al, 2014) and favor uneven-aged spruce and mixed stands through silvicultural practices such as partial cuttings (Bergeron et al, 2017). Integrative multiple-disturbance research is needed to better understand the climatic and ecological context of insect outbreaks and to identify the type of interactions that occur during these events; as such, adequate management strategies can be developed in accordance with the forest structure at regional and local scales.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, sylvicultural practices aim to imitate fire disturbances promoting large clearcuts (Hunter, 1993; National Forest Database [N.F.D], 2016. In order to reduce boreal forest vulnerability to SBW outbreaks, some authors proposed to adapt sylvicultural treatments and forest management promoting the harvesting of the most susceptible stands such as mature fir stands (MacLean, 1980, 1996; Sainte-Marie et al, 2014) and favor uneven-aged spruce and mixed stands through silvicultural practices such as partial cuttings (Bergeron et al, 2017). Integrative multiple-disturbance research is needed to better understand the climatic and ecological context of insect outbreaks and to identify the type of interactions that occur during these events; as such, adequate management strategies can be developed in accordance with the forest structure at regional and local scales.…”
Section: Discussionmentioning
confidence: 99%
“…There are several strategies proposed to minimize risk of commercial timber loss due to SBW prior to an outbreak (Sainte-Marie et al, 2015). Such strategies include shifting species composition toward less susceptible commercial species like spruce (Picea spp.)…”
Section: Discussionmentioning
confidence: 99%
“…For a company whose mills run on softwoods, shifting forest composition to hardwoods would immediately affect timber supply. A study in eastern Canada showed that replacing balsam fir stems (the primary host of the spruce budworm) with hardwoods would reduce total conifer yield while increasing resistance to the spruce budworm [ 171 ]. In this work, the protective effect of hardwoods on residual fir was less than the softwood timber supply lost to hardwoods.…”
Section: Barriers To Implementing Host Reductionmentioning
confidence: 99%